Analysis and Design of a Cooling Tower Considering Wind Pressure and Thermal Effect Using Staad.Pro A Review - Vinay Kumar Sinha; Pradeep Kumar Nirmal; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2021)
Cooling tower is an integral part of every thermal power generation plant. Basically cooling tower are heat rejection devices used to transfer heat from hot water to the atmosphere air. Investigation involves experimental and two-dimensional computational fluid dynamics analysis of an actual industry operated cooling tower. Inlet water temperature and mass flow rate of water and air are having main influence on the performance of counter flow induced draft cooling tower. In cooling tower water is made to trickle down drop by drop, or form a thin layer over flat surface so that it comes into direct contact with air moving upwards in opposite direction. The heat transfer from the water to the air steam raises the air’s temperature and its relative humidity to 100% and this air is discharged to the atmosphere. Likewise other parameters such as range, tower characteristic ratio can also be increased considerably, pressure at outer region, temperature variations. In this paper we are presenting review of literatures related to analysis of water tanks.
Keywords: Nonlinear Static Analysis; Deflection Cooling Tower; Analysis; Thermal; Displacement; Forces; Moment